The Implementation of the Service Marketing Mix (7P) as a Service Marketing Strategy in Hospitals: A Literature Review - Uci Intan Permatasari; Ulfa Novirwan; Umchudloh Umchudloh; Unggul Prestiaji; Rohendi Rohendi (Jurnal Indonesia Sosial Sains, 2026)
Hospitals as service organizations face increasingly complex challenges in managing healthcare service marketing amid rising patient expectations regarding service quality and experience. One relevant approach in hospital service marketing is the service marketing mix (7P), which includes product, price, place, promotion, people, process, and physical evidence. However, existing studies indicate that the implementation of the service marketing mix (7P) in hospitals remains largely partial and lacks strategic integration. This study aims to analyze the implementation of the service marketing mix (7P) as a service marketing strategy in hospitals through a literature review approach. A narrative–analytical literature review was conducted by examining 20 relevant national and international journal articles retrieved from the Google Scholar, Scopus, and Garuda databases. The analysis employed a thematic approach to identify implementation patterns, the role of each 7P element, and the implications of service marketing mix integration for patient experience, satisfaction, and loyalty. The findings reveal that although the service marketing mix (7P) has been widely adopted in hospital marketing studies, its practical implementation remains insufficiently integrated. The people, process, and physical evidence elements play a dominant role in shaping patient experience, while the lack of integration among the 7P elements contributes to service inconsistency and low patient loyalty. This study highlights the importance of positioning the service marketing mix (7P) as an integrated, patient-experience-oriented service marketing strategy to enhance marketing effectiveness and hospital competitiveness.